Optimization of Authentication Methods for Processed Chicken Meat Products Based on ND5 Gene qPCR - Afifatul Achyar; Fira Safitri; Yusni Atifah; Siska Alicia Farma; Dwi Hilda Putri; Yuni Ahda (Halal Research, 2025)
Consumers have the right to correct information about the products they consume. One example of a food product that is vulnerable to counterfeiting is chicken nuggets. To overcome this problem, qPCR can be an effective solution. Previous research has designed primers targeting the chicken ND5 gene. However, the PCR conditions for this primer pair have never been optimized. This research aims to optimize qPCR conditions and carry out chicken nugget authentication trials. Genomic DNA was isolated from five weight variations of chicken meat samples as a qPCR standard curve and three chicken nugget samples. Optimizing the annealing temperature with gradient PCR gave the best results at a temperature of 57.6OC. The results of the authentication test showed that the chicken meat content in TD nuggets was 54.7%, C nuggets 43.8%, and D nuggets 37.3%. This value is still in accordance with the Indonesian National Standard (SNI).